Estimates of cooling effect and energy savings for a cool white coating used on the roof of scale model buildings. (February 2019) - Qu, J; Guan, S; Qin, J; Zhang, W; Li, Y; Zhang, T
Abstract: The solar reflectance and thermal emittance of uninsulated scale model buildings in Beijing were measured in the laboratory and the actual outdoor environment. The solar reflectance index (SRI), roof surface temperature and energy savings were estimated using DOE roof saving calculator. The roof albedo measured in the field tests is independent of the inverted pyranometer height. A 0.493 increase in solar reflectance (laboratory measurements) yields SRI increase by 67.5, roof surface temperature reduction by 25.5 °C, annual peak demand reduction by 0.1 kWm -2 yr -1, and annual net energy savings by 6.8 kWhm -2 yr -1, while a 0.459 increase in roof albedo (laboratory measurements) generates SRI increase by 62.3, roof surface temperature reduction by 23.5 °C, annual peak demand reduction by 0.1 kWm -2 yr -1, and annual net energy savings by 6.4 kWhm -2 yr -1 . At the city scale, these savings would reduce emissions from China's power plants by 60 kton CO2, 1.1 kton NOx, 2.1 kton SO2 and 19.4 kton carbon dust for the laboratory tests and by 56.6 kton CO2, 1.0 kton NOx, 2.0 kton SO2 and 18.3 kton carbon dust for the field tests.